Forgotten saints history, power, and politics in the making of modern Morocco - Bazzaz, Sahar (Harvard Middle Eastern monographs, 2010)
In 1894, a young Muslim mystic named Muhammad al-Kattani abandoned his life of asceticism to preach Islamic revival and jihad against the French. Through his activism, he mobilized a socially diverse coalition of Moroccans who called for resistance against French colonization. On a broader level, it offers alternative ways to understand the responses of Muslim societies to the challenges of globalization, European imperialism, and Western modernity while demonstrating that at the heart of anti-colonialism and nationalism lay a much deeper internal struggle over emerging forms of power and authority in the era of nation-state formation.